Une fondation Polanyi : un projet toujours actuel, A Polanyi Foundation : Still Up To Date - Caillé, Alain (Revue du MAUSS, 2007)
La pensée de Polanyi peut être vue comme une sorte de lieu géométrique entre des courants de pensée de gauche très divers, de la gauche de gauche au centre gauche. Cet article montre comment, entre 1995 et 1999, le nom de Polanyi a en effet servi de point de ralliement à des dizaines d’intellectuels (sociologues, économistes, philosophes...) connus en France et en Europe, ce qui n’a pas été sans impact politique. Une perspective toujours d’actualité ?, Polanyi’s throught can be seen as some sort of smallest denominator common to diverse spheres of the Left ranging from ultra to central Left. The article shows how between 1995 and 1999 Polany’s name has permitted to gather dozens of well-known intellectuals (sociologists, economists, philosophers) in France and in Europe and how this gathering has had some political impact. A still urgent perspective ?
Keywords: plural economy; radical social democracy; social-démocratie radicale; économie plurielle

Il sofisma economicista: intorno a Karl Polanyi - Caillé, Alain (sn, 2011)
KM translate: "The economic sophistry" and "The two meanings of" economic "", short writings by Karl Polanyi published here partially in a version taken from the French magazine MAUSS, represent a wonderful example of critical synthesis and set of depth of analysis, an analysis that comes to the conviction of the anthropological and social disaster caused not only by liberalism, but even more by the fallacy of an entire system of thought, economic science, which seeks to justify and support it. In support of the interesting pages of Polanyi, this book presents two contributions, respectively by Alain Caillé with Jean-Louis Laville and Jerome Maucourant, which, in addition to quickly presenting the intellectual biography of the Hungarian philosopher, clarify the extreme relevance of his critique of capitalism and the society of the markets. Polanyi emerges as an economist from the solid historical and anthropological foundations that, with his work, has been able to dismantle the apparently solid building of the classical economy to reveal its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century.
Keywords: business & economics; economic theory

Actualité de Karl Polanyi, The Actuality of Karl Polanyi - Caillé, Alain; Laville, Jean-Louis (Revue du MAUSS, 2007)
Que peut-on retenir de l’œuvre de K. Polanyi en comparaison, notamment, de celles de Marx ou de Weber ? Cet article fait le point à la fois sur les contributions historiques et anthropologiques de Polanyi à l’histoire du marché et sur son aspiration à un socialisme associationniste, et il conclut que, audelà des nécessaires rectifications et actualisations, K. Polanyi reste la source d’inspiration principale pour un socialisme radical à visage humaniste., What must be kept of K. Polanyi’s legacy as compared, especially, to those of Marx or Weber ? This article provides an evaluation both of the anthropological and historical contributions of Polanyi to the history of market(s) and of the present meaning of his advocacy of an associationist socialism. It concludes that, once the necessary corrections and rectifications are made, Polany remains our main resource to think a radical and democratic socialism with a humanist face.
Keywords: capitalism; capitalisme; democracy; démocratie; marché; markets; socialisme associationniste; solidarity economy; économie solidaire